(3YeOI GdEUdGM aj Yed UfGYI GdLQGMs - (3jYbhH Hf ESMGb GdeSjMj Gdedcj GdcQcj GHf Gdba, CHh GdaQL,J (B685 (3g` s
(3ChdgG (B:s
(3hHYO abO TcG Edi HYV LQGMi ReGffG bdI EgJeGe CQHGH gPG Gdaf HCeQ gPg GdUfGYI hGf hGMOkG efge de jYQa Shi JQcjH s
(3BNQgG (B:s
(3Ke jDNP ScQ fbj hRf QWdjf jOb hjVGa Edjg ChdoG aChd hjLYd aj TeS MGQI KdKjf jhekG hojSJYed hGddg SHMGfg CYde s
(3fSNI NGeSI cGdSGHbIs
(3cJHJ YfGhjfgG HGdMeQIs
(3hGdfSNI oebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B161 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs